2022
DOI: 10.1037/sgd0000479
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of health care discrimination among transgender and gender nonconforming people of color: A latent class analysis.

Abstract: There is a paucity of research on the within-group differences in experiences of health care discrimination among transgender and gender nonconforming people of color. This study employs latent class analysis to identify mutually exclusive subgroups of TGNC POC based on responses to measures of health care discrimination. The association between demographic and health indicators and subgroup membership was also examined. Four subgroups were found: the low discrimination subgroup marked by a low probability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 42 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…This study expands the literature about TGI individuals’ healthcare experiences and utilization behaviors [ 1 , 2 , 3 , 4 , 10 , 12 , 18 ]; by documenting high rates of discrimination directed at TGI individuals in childhood, ranging from abusive (e.g., harsh language and refusal of care) to non-inclusive (e.g., lack of identity representation on medical documentation and forms). These findings indicate that TGI youth’s exposure to healthcare discrimination might diminish trust in healthcare institutions and providers necessary for their engagement in care (e.g., preventative care), trust in provider recommendations (e.g., vaccinations), and the improvement of their health outcomes (e.g., disease management) in adulthood.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This study expands the literature about TGI individuals’ healthcare experiences and utilization behaviors [ 1 , 2 , 3 , 4 , 10 , 12 , 18 ]; by documenting high rates of discrimination directed at TGI individuals in childhood, ranging from abusive (e.g., harsh language and refusal of care) to non-inclusive (e.g., lack of identity representation on medical documentation and forms). These findings indicate that TGI youth’s exposure to healthcare discrimination might diminish trust in healthcare institutions and providers necessary for their engagement in care (e.g., preventative care), trust in provider recommendations (e.g., vaccinations), and the improvement of their health outcomes (e.g., disease management) in adulthood.…”
Section: Discussionmentioning
confidence: 55%
“…Gender identity-related stigmatization, discrimination, and erasure in healthcare settings serve as central barriers to the accessibility and utilization of healthcare for individuals who embody transgender and gender independent (TGI) identities [ 1 , 2 ]. TGI individuals encounter direct and indirect forms of discrimination in healthcare settings, including healthcare providers’ lack of knowledge about their gender identities and healthcare needs, verbal and physical harassment, abuse, and denial of care [ 1 , 3 ]. Fear-based avoidance of healthcare among TGI individuals reporting exposure to past year healthcare discrimination has been documented [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trans people of color in the United States exist at the intersection of both racialized and gendered oppression, creating unique and complex experiences balancing survival in a white supremacist, cisnormative society and living as one’s authentic self 1 . In line with intersectionality (Crenshaw, 1991), it is important to investigate how trans people of color’s negative health outcomes are influenced by structural and interpersonal identity-based discriminatory forces such as cissexism, racism, as well as gendered racism (Alizaga et al 2022). Related literature, seeking to avoid a solely deficits-focused picture of this community, has simultaneously noted how trans people of color have tremendous strengths, leveraging resilience to navigate intersectional oppression (Singh, 2013; Singh et al, 2020).…”
Section: Intersectionality and The Experiences Of Trans People Of Colormentioning
confidence: 99%
“…Other studies have revealed similar and parallel findings. For example, Alizaga et al (2021) demonstrated that trans men were 3 times as likely to report anticipated health care discrimination and were more likely to have experienced discrimination when compared with their trans counterparts. Stanton et al (2021) reported that among a gender-expansive sample, trans men, AFAB nonbinary individuals, and trans women were most likely to report attending one behavioral health appointment.…”
Section: Introductionmentioning
confidence: 99%